A Perspective Review on Hyperledger Fabric Access Control System - Raj, Stephen Jebamalai (Recent Research Reviews Journal, 2022)
Blockchain technology has enormous potential and is currently seen as a new technical trend with a quickening growth rate. Supply chain, health care, and finances are just a few of the application areas wherein blockchain-based systems are gaining interest. Whenever it comes to public and private management, data integrity is crucial and becoming more essential. Data integrity can be achieved in an access control system which is built on the blockchain. By using encryption protocols, access controls, and cryptography techniques, the Hyper ledger Fabric is created to be safe against unauthorised access and use. Systems for access control exist to safeguard resources against unwanted access. Platforms for blockchain systems, such as Hyperledger Fabric, are built with data integrity, complete transparency, and confidentiality. This article provides an in-depth analysis of a Hyperledger enterprise blockchain technology.
Keywords: Blockchain; public and private management; data integrity; Hyperledger Fabric